P145 Arterial Stiffness and Left Ventricular Diastolic Function in Patients with Metabolic Syndrome: Longitudinal Study - Solovjova, Svetlana; Ryliskyte, Ligita; Puronaite, Roma; Celutkiene, Jelena; Laucevicius, Aleksandras; Badariene, Jolita; Slivovskaja, Ieva; Rinkuniene, Egidija (Artery research, 2018)
Aim To evaluate the relation between arterial stiffness and left ventricular diastolic dysfunction (LVDD) in metabolic syndrome (MetS) patients during more than 3 years observation period (average was 3,8 years). Methods This longitudinal study enrolled 573 subjects (aged 53,4 ± 6 years, 63% female, 76% hypertensive) from the Lithuanian High Cardiovascular Risk Primary Prevention Programme1, without overt atherosclerotic disease and systolic LV dysfunction. Arterial stiffness parameters (carotid-to-femoral pulse wave velocity(cfPWV), augmentation index (AIxHR75), mean aortic pressure(mAP), central pulse pressure(cPP) were assessed by applanation tonometry. Diastolic function (LVDF) was defined according to the 2016 ESC Guidelines for diagnosis and treatment of acute and chronic heart failure. Results In presented cohort most of study subjects had LVDD at first visit (n = 418, n = 325 impaired relaxation, n = 92 pseudonormalisation, n = 1 restrictive LVDD). During the observation LVDF didn’t change in 337 (GR1 ), deteriorated in 110 (GR2), improved in 126 (GR0) participants. We found significant alterations of arterial and diastolic function parameters(mean): cfPWV 8,55 ± 1,4 vs 8,7 ± 1,6 m/s; AIxHR75 22,8 ± 10,4 vs 24,3 ± 10,8%; mAP 105,3 ± 10,4 vs 101,5±14,8 mmHg; cPP 42,6 ± 9,9 vs 43,3 ± 10,6 mmHg; E/A ratio 1 ± 0,3 vs 0,93 ± 0,2; E/e’mean ratio 10,4 ± 3,5 vs 9,4 ± 2,9; E/e’septal 11,9 ± 4,1 vs 10, 9 ± 3,2; MMI105 ± 22,7 vs 99 ± 24,1 (p< 0,05 for all). Significant correlations were found between initial arterial indices and alterations of LVDF: in GR1 with E/Aratio (rcfPWV = –0.176); in GR0 with E/e’mean (rcfPWV = –0.163, r mAP = –0.171). To clarify the relation between LVDD and arterial stiffness the conditional inference trees analysis was used. Only cfPWV, mAP, heart rate and BMI were significant for presence of LVDD. Conclusion Carotid-to-femoral PWV, the biomarker of vascular damage, is significant determinant of LV diastolic dysfunction in MetS patients. Arterial stiffness is a possible causal link to development of LV diastolic dysfunction.